EKSPANSI PASAR MELALUI DIGITALISASI BISNIS PADA USAHA PRODUKTIF PEREMPUAN DESA PAKIS REJO - Dwi Budi Santoso; Farah Wulandari Pangestuty; Fina Nidaul Mahalli (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2023)
The exponential growth of technology compellingly compels MSMEs to adapt and seize opportunities particularly for potential MSMEs Pakisrejo Village, located in the Blitar Regency, is a developed village with MSMEs potential. Processed products such as Lompong chips, taro stalks utilized as animal feed, orange candy, and coconut sugar are among the most prominent categories of MSME enterprises. Nonetheless, lack of understanding regarding digitalization and restricted market access impede the growth of MSMEs in these villages. The objective of this service community program is to foster the growth MSMEs, with a particular focus on enhancing their market penetration through the strategic utilization of digital marketing. This initiative recognizes the potential of productive businesses to achieve this goal. The community service program step including Pre-implementation socialization, service preparation, service implementation, mentoring, and result evaluation. The result finding stated that this service community program was a success because 60% MSMEs that attended the workshop demonstrated the ability to apply the information that had been explained during the post-test. This is also accompanied by a surge in sales, as the utilization of a marketplace expands market penetration, enabling the product to reach a significantly broader spectrum of consumers.